The fallacy of objective security and its consequences - Guillén-Lasierra, Francesc (International e-journal of criminal sciences, 2021)
The determination that the main ground for citizens’ security perception was not linked (directly and uniquely) with crime had, as a consequence, the definition of two kinds of security: the objective one, empirically demonstrable, truly existing, and the other one, the subjective, volatile und unreal, related to population’s security perception. The later, although not necessarily based on crime, had to be taken into account because it influences people’s conducts. This article aims to evidence that the so called "objective security" (security measured from objective, neutral, parameters) depends on a lot of subjectivities from diverse actors, on which risks are considered acceptable, the ground values considered to need protection, the circumstances that influence the main actors’ decisions making procedures, the rules from assurance companies, resources in police stations, or the time coincidence of incidents that require police attention or response. That’s to say: Objective security is also quite subjective. Nevertheless, the fact that security be mainly composed of subjective elements doesn’t mean that the sources used to ascertain the traditional objective security (surveys and police statistics) are not relevant anymore, or that the origin of insecurity is not important in order to design policies and strategies as response to it.